2018
DOI: 10.1123/pes.2016-0226
|View full text |Cite
|
Sign up to set email alerts
|

Hip Flexor and Knee Extensor Muscularity Are Associated With Sprint Performance in Sprint-Trained Preadolescent Boys

Abstract: These findings suggest that greater hip flexor and knee extensor muscularity in male preadolescent sprinters may help achieve superior sprint performance by potentially enhancing their moments, which may be induced by increased step frequency rather than step length during sprinting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 34 publications
3
41
1
Order By: Relevance
“…However, Stafilidis and Arampatzis (2007) found no significant difference in the muscle thickness of the plantar flexors between superior and inferior adult sprinters. Furthermore, a recent study showed no significant correlation between the muscle size of plantar flexors and the sprint time; the authors suggested that, in prepubescent boys, the contribution of the size of the lower leg muscles to sprint performance is relatively low compared to that of the trunk or thigh muscles . Our results support these findings, an increased muscle size of the thigh results in improved sprint performance; however, the importance of the muscle size of the plantar flexors may be low in prepubescent sprinters.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, Stafilidis and Arampatzis (2007) found no significant difference in the muscle thickness of the plantar flexors between superior and inferior adult sprinters. Furthermore, a recent study showed no significant correlation between the muscle size of plantar flexors and the sprint time; the authors suggested that, in prepubescent boys, the contribution of the size of the lower leg muscles to sprint performance is relatively low compared to that of the trunk or thigh muscles . Our results support these findings, an increased muscle size of the thigh results in improved sprint performance; however, the importance of the muscle size of the plantar flexors may be low in prepubescent sprinters.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding muscle morphology in junior sprinters, only two studies have investigated the impact of the muscle size of the lower limb on the sprint performance (50 m sprint time or mean velocity for a 100 m race, respectively); both studies demonstrated that an increased muscle size of the quadriceps femoris is correlated with improved sprint performance. In the current study, we identified a similar relationship between the sprint time and muscle thickness of the VL (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations